Efektivitas E Learning Mata Kuliah Kewirausahaan di Universitas Negeri Padang pada Masa Pandemi COVID 19: The Effectiveness E Learning of Entrepreneurship Courses at State University of Padang during the COVID 19 Pandemic - Dewi, Muharika; Rosalina, Linda; Ernawati, Ernawati (Indonesian Journal of Informatic Research and Software Engineering (IJIRSE), 2021)
This study aims to identify the effectiveness of entrepreneurship learning using website media in e learning conducted at Universitas Negeri Padang during the COVID 19 pandemic. The research methodology uses a quantitative approach, evaluation is carried out on 307 samples who are students who have participated in Entrepreneurship learning using e learning. during the COVID 19 pandemic, research is an evaluation type research to present recommendations for implementing learning programs. The research instrument used a set of questions about cognitive, affective and psychomotor abilities to adjust the Entrepreneurship learning curriculum at Universitas Negeri Padang. The data analysis used the percentage technique and the calculation of the difference in score values. The results showed that cognitive, affective and psychomotor have an average increase, but students have the final knowledge achievement at a score of 72 (cognitive), 79 (affective) and 74 (psychomotor), which means that the final learning outcomes of students have not reached value limit categorized as good at an average score of> 80. Thus the recommendation for the results of this evaluation is that it is necessary to improve the performance of the e learning learning program to achieve better learning outcomes through educational factors which include the quality of educators, media and increased student learning motivation.